Translanguaging in fremdsprachigen literarischen Texten sowie beim Lesen fremdsprachiger literarischer Texte - Jazbec, Saša; Löwenkamp, Sarah (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
Translanguaging is an approach that has been recognized in theory, particularly in bilingual research, for approximately 30 years. It is based on the premise that multilingual people have a unifiedlinguistic repertoire that they use flexibly and that encompasses all their languages (native language, foreign languages, second language, linguistic varieties). It is a multilingual practice that all people are familiar with and practise in non-intentional contexts or in private. This fluid use of resources within the linguistic repertoire challenges the limits of monolingualism, monolingual standards, and Codeswitching in society and education, while simultaneously overcoming them. Translingual practices differ at the receptive level (translanguaging is used in oral communication) and at the productive level (translanguaging results in written texts). This article will address both levels: literary texts that can be described as translingual products (e.g., Tawada, Krivokapić) and the translingual- oriented reception of literary texts. The focus is primarily on the research question relevant to literature didactics, namely, how translanguaging practices (can) improve students’ engagement and language comprehension when analysing foreign-language literary texts.